Author Correction: Generation and characterization of ultrathin free-flowing liquid sheets - Koralek, Jake D; Kim, Jongjin B; Brůža, Petr; Curry, Chandra B; Chen, Zhijiang; Bechtel, Hans A; Cordones, Amy A; Sperling, Philipp; Toleikis, Sven; Kern, Jan F; Moeller, Stefan P; Glenzer, Siegfried H; et al. (Nature communications, 2019)
The original version of this Article contained an error in Eq. (1). This has been corrected in both the PDF and HTML versions of the Article.